Modeling on number of children ever born and its determinants among married women of reproductive age in Ethiopia: A Poisson regression analysis. Issue 3 (March 2023) - Cherie, Niguss; Getacher, Lemma; Belay, Alemayehu; Gultie, Teklemariam; Mekuria, Aleme; Sileshi, Samrawit; Degu, Getu
Abstract: Background: One of the main components of population dynamics that determine the size, structure, and composition of a country's population is the number of ever-born children. Psychological, economic, social, and demographic factors all have a strong influence on and predict it. However, there is little information on its current status in Ethiopia. As a result, modeling the number of children ever born and its determinants is critical for the Ethiopian government to develop appropriate policies and programs. Methods: A total of 3260 eligible women were used as a study sample in this study to assess the number of children ever born and determinants among married reproductive age women in Ethiopia. Secondary data were culled from the 2019 Ethiopian Demography and Health Survey datasets. The factors associated with the number of children born were identified using a Poisson regression model (CEB). Results: The average number of children per mother was 6.09, with a standard deviation of 8.74. There were 2432 (74.6%) rural residents among the total respondents, 2402 (73.7%) have no formal education, and three out of five women are not currently working. The participants' average age was 41.66, with a standard deviation of 3.88. When compared to urban residents, the number of CEB for rural residents is 1.37 times higher. When compared to women with no education, the number of CEB for women with higher education was reduced by 48%. For every unit increase in respondents' current age, the percent change in the number of children ever born increases by 2.4%. For every unit increase in the family's wealth index status, the percent change in the number of children ever born decreases by 1.7%. Conclusion: When compared to the target of Ethiopia's health transformation plan, the average number of children born is higher. Improving the household wealth index, women's education, and employment status all contribute to a reduction in the number of CEB, which is important in balancing population growth with natural capacity and the country's economic development.